Co-immobilization of Palm and DNase I for the development of an effective anti-infective coating for catheter surfaces - Alves, D. (2016)
Biomaterial-associated infections, in particular, catheter-associated infections (CAI) are a major problem in clinical practice due to their ability to resist antimicrobial treatment and the host immune system. This study aimed to co-immobilize the antimicrobial lipopeptide Palm and the enzyme DNase I to introduce both antimicrobial and anti-adhesive functionalities to polydimethylsiloxane (PDMS) material, using dopamine chemistry. Surface characterization confirmed the immobilization of both compounds and no leaching of Palm from the surfaces for up to 5 days. Co-immobilization of both agents resulted in a bifunctional coating with excellent surface antimicrobial and anti-biofilm properties against both Staphylococcus aureus and Pseudomonas aeruginosa. The modified surfaces demonstrated superior biocompatibility. To better discriminate co-adhesion of both species on modified surfaces, PNA FISH (Fluorescence in situ hybridization using peptide nucleic acid probes) was employed, and results showed that P. aeruginosa was the dominant organism, with S. aureus adhering afterwards on P. aeruginosa agglomerates. Furthermore, Palm immobilization exhibited no propensity to develop bacterial resistance, as opposite to the immobilization of an antibiotic. The overall results highlighted that co-immobilization of Palm and DNase I holds great potential to be applied in the development of catheters.